CASE STUDY OF POWER SHARING CONTROLLER WITH THE USAGE OF DROOP CONTROL METHOD TO ANALYZE MANAGEMENT ENERGY SYSTEM IN ISLANDING MODE - Nova Zainur Rifki; Irrine Budi Sulistiawati; Awan Uji Krismanto (Journal of Sustainable Technology and Applied Science (JSTAS), 2025)
Microgrid as Renewable Energy in electricity is usually referred as Distributed Generation (DG). This research analyzes power sharing in a DC Microgrid using the droop control method in islanding mode, which is when the DC Microgrid operates separately from the main grid (PLN), and the load is fully supplied by DG. This Power Sharing Controller ensures that the power generated by each DG is in accordance with the system's requirements. This research uses Matlab Simulink software for its simulations. The DC Microgrid consists of three buck-boost converters connected in parallel. The power capacity and droop value of each buck-boost converter are adjusted according to the case. The test results showed that the determination of the droop value affects the power generated by the buck-boost converter. The smaller the droop value, the greater the power produced, and vice versa. Of the three cases simulated in the first case with an even load distribution on the buck-boost equal to a load increase of 1000w, there is an increase in power to 334 w and a current of 33.4 A, while in the second case with a load increase of 1000w, there is a power variation between 300-360 w and a current in the range of 3.6 to 30 amperes. While in case 3 a load increase of 1000 w buck-boost produces power at a value of 325-345w.